2016
DOI: 10.1039/c5nj03446a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of synergic cooperation on optical and photoelectrochemical properties of CeO2–MnO composite thin films

Abstract: Low-temperature (475 °C) fabrication of CeO2–MnO composite thin films having a band gap of 2.5 eV by AACVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…We have investigated several manganese oxide based photocatalysts such as Mn 2 O 3 -4TiO 2 , 20 Mn 2 O 3 -TiO 2 , 21 MnO 2 -CeO 22 and solid solution of MnZnO 3 23 and found them advantageous for PEC water splitting applications. These studies revealed that the coupling of two semiconductors might result in improved interfacial charge transfer thereby minimizing charge recombination, lowering the band gap and ultimately boosting photo-activity in the visible region.…”
Section: Introductionmentioning
confidence: 99%
“…We have investigated several manganese oxide based photocatalysts such as Mn 2 O 3 -4TiO 2 , 20 Mn 2 O 3 -TiO 2 , 21 MnO 2 -CeO 22 and solid solution of MnZnO 3 23 and found them advantageous for PEC water splitting applications. These studies revealed that the coupling of two semiconductors might result in improved interfacial charge transfer thereby minimizing charge recombination, lowering the band gap and ultimately boosting photo-activity in the visible region.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the formation of pores in the as-deposited film can be interpreted by the basis of homogeneous and heterogeneous nucleation processes similar to the metal oxide composite-based thin films prepared using an aerosol-assisted chemical vapor deposition technique. [57][58][59] In the present study, the deposition temperature (substrate temperature) was kept at 400 1C, producing the mixture of Cu oxide and Bi subnitrate that have different pyrolysis temperatures (see Fig. S5, ESI †).…”
Section: Structural and Morphological Properties Of Cubi 2 Omentioning
confidence: 99%
“…The change in thin microstructure with temperature was explained based on homogeneous and heterogeneous nucleation. [67]…”
Section: Temperaturementioning
confidence: 99%
“…The schematic representation for the photoelectrocatalytic activity of Mn 2 O 3 −TiO 2 composite thin films and the corresponding photoelectrochemical responses are depicted in Figure 3. In another study by Mansoor et al., [67] CeO 2 −MnO composite thin films were deposited by using dual precursor strategy, i. e., a self‐designed cerium complex, [Ce(TFA) 4 ] [dmaeH]+ and commercially available Mn(OAc) 2 (OAc=acetate). Thin films were grown at 450, 475, and 500 °C.…”
Section: Aacvd Factors Affecting the Structural Outcomesmentioning
confidence: 99%
See 1 more Smart Citation